Overcoming the Quarter-Life Crisis: The Role of Eclectic Therapy, Support Groups, and Expressive Writing for Emerging Adults - Maulida, Faza; Wati, Rinda Kumala; Uzzakiyah, Hasna (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The quarter-life crisis is a phase of emotional instability and uncertainty about life direction commonly experienced by individuals in emerging adulthood. This phase is characterized by confusion regarding life goals, pressure to achieve certain milestones, and demands related to the transition toward independence, all of which may increase psychological stress and hinder adaptive functioning. These conditions highlight the need for effective and accessible psychological interventions for this age group. This study aims to examine the effectiveness of an eclectic intervention combining support group therapy and expressive writing in reducing quarter-life crisis levels among individuals in emerging adulthood. The study employed a pre-experimental one-group pre-test post-test design with purposive sampling. Seven participants who met the criteria for experiencing a quarter-life crisis took part in the intervention. Data were analyzed using a paired sample t-test. The results showed a significant difference in quarter-life crisis levels before and after the intervention (p = 0.008; p < 0.05). These findings indicate that support group therapy combined with expressive writing is effective in reducing the quarter-life crisis among emerging adults. The implications of this study emphasize that group-based eclectic interventions can serve as an alternative psychological strategy to help young adults navigate the challenges associated with the quarter-life crisis.